2005
DOI: 10.1352/0895-8017(2005)110[253:eomric]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of Mental Retardation in Children Referred to a Tertiary Care Center: A Prospective Study

Abstract: A prospective assessment following a step-wise protocol in 281 patients with unexplained cognitive delay was used to assess diagnostic possibilities. Diagnostic procedures were complex and required a multidisciplinary approach. One third of diagnoses was established based on clinical history and physical exam only; for another third, clinical history and physical exam provided essential clues for additional investigations; and a third were established by additional investigations only. The likelihood to reach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
73
0
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 28 publications
4
73
0
6
Order By: Relevance
“…This association was not found in an earlier study. 30 Intrauterine infections may be difficult to confirm in older children and some genetic syndromes may not manifest all the dysmorphic features till a later age. Severity of intellectual disability or GDD did not influence the diagnostic yield in our study, a finding consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This association was not found in an earlier study. 30 Intrauterine infections may be difficult to confirm in older children and some genetic syndromes may not manifest all the dysmorphic features till a later age. Severity of intellectual disability or GDD did not influence the diagnostic yield in our study, a finding consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Severity of intellectual disability or GDD did not influence the diagnostic yield in our study, a finding consistent with previous studies. 3,30 We found that the combination of clinical history and examination to be the most useful tool in arriving at a diagnosis. Even though we observed strict criteria for final diagnosis incorporating both clinical features and investigations in almost three quarters of the patients, clinical history and examination gave important clues suggestive of other conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Genetic causes account for 17.4-47.1% of cases, with reported frequencies also varying on the basis of the different techniques used for analysis. 15,16 Several years ago, microarray platforms were used for the first time in clinical genetics, showing that abnormalities in genomic copy number account for about 10-15% of patients affected by MR, especially when it is associated with multiple congenital anomalies (MCA) and/or dysmorphism. 17 Microarrays represent a robust and high-resolution method of analysis.…”
Section: Introductionmentioning
confidence: 99%
“…2 As part of a large collaborative project to identify genes involved in autosomal recessive MR, 3 we performed linkage analysis in an Iranian family with three affected siblings who suffered from an apparently novel syndromic form of MR associated with cataract, coloboma and kyphosis. Here, we report on the clinical details of the patients and the identification of a gene locus in the pericentromeric region of chromosome 4.…”
Section: Introductionmentioning
confidence: 99%